A Delphi survey of practitioner's understanding of mental capacity. Issue 5 (22nd November 2018) - Clerk, George; Schaub, Jason; Hancock, David; Martin, Colin
Abstract : Purpose: The purpose of this paper is to present the findings of a study considering the application of the Mental Capacity Act and Deprivation of Liberty Safeguards (DoLS). Practitioners from a range of professions were recruited to provide their views of how to respond to a variety of scenarios. GPs, nurses, social workers, physio/occupational therapists and care assistants were recruited to participate. Design/methodology/approach: This study used the Delphi method to elicit participant views and generate consensus of opinion. The Delphi method recommends a large sample for heterogeneous groups, and round one had 98 participants from six different professional groups. Findings: Participants did not respond consistently to the scenarios, but disagreed most significantly when patient decisions conflicted with clinical advice, and when to conduct a capacity assessment. These responses suggest that clinical responses vary significantly between individuals (even within settings or professions), and that the application of Mental Capacity Act (MCA) is complicated and nuanced, requiring time for reflection to avoid paternalistic clinical interventions. Originality/value: Previous studies have not used a Delphi method to consider the application of MCA/DoLS. Because of this methods focus on developing consensus, it is uniquely suited to considering this practice issue. As a result, these findings present more developed understanding of the complexity and challenges for practitioner responses to some relatively common clinical scenarios, suggesting the need for greater clarity for practitioners.